Transform f(x) to f(x ± a)​

2 .       f(x) to f(x ± a ) , when f(x) is given

 

Where  ‘a’ is positive constant.

2.1   f(x) transforms to f(x – a) , Where  ‘a’ is positive constant.

Shift the graph of f(x) through ‘a’ unit towards right direction.

Example 1.

To draw a graph  y = | x | to y = |x ± 1 |

Draw graph of y = |x| —> |x – 1|

As discussed  f(x) —> f(x – a) , Where  ‘a’ is positive constant.

Shift the graph of y = |x| through ‘1’ unit towards right direction.

graph transform y=|x| to y=|x-1|

2.2  f(x) transforms to f(x + a) , Where  ‘a’ is positive constant.

Shift the graph of f(x) through ‘a’ unit towards left direction.

Draw graph of y = |x| —> |x + 1|

As discussed  f(x) —> f(x + a) , Where  ‘a’ is positive constant.

Shift the graph of f(x) through ‘1’ unit towards left direction.

Transform f(x) to f(x ± a)​ : y=|x+1|